Structural insights on anti-biofilm mechanism of heated slightly acidic electrolyzed water technology against multi-resistant Staphylococcus aureus biofilm on food contact surface - Pianpian Yan; Ramachandran Chelliah; Kyoung Hee Jo; Xiuqin Chen; Akanksha Tyagi; Hyeon Yeong Jo; Fazle Elahi; Nam Chan Woo; Min Seung Wook; Deog Hwan Oh (Food Science and Human Wellness)
Slightly acidic electrolyzed water (SAEW) has proven to be an efficient and novel sanitizer in food and agriculture field. This study assessed the efficacy of SAEW (30 mg/L) at 40 ℃ on the inactivation of foodborne pathogens and detachment of multi-resistant Staphylococcus aureus (MRSA) biofilm. Furthermore, the underlying mechanism of MRSA biofilm under heated SAEW at 40 ℃ treatment on metabolic profiles was investigated. The results showed that the heated SAEW at 40 ℃ significantly effectively against foodborne pathogens of 1.96–7.56 (lg (CFU/g)) reduction in pork, chicken, spinach, and lettuce. The heated SAEW at 40 ℃ treatment significantly reduced MRSA biofilm cells by 2.41 (lg (CFU/cm2)). The synergistic effect of SAEW treatment showed intense anti-biofilm activity in decreasing cell density and impairing biofilm cell membranes. Global metabolic response of MRSA biofilms, treated by SAEW at 40 ℃, revealed the alterations of intracellular metabolites, including amino acids, organic acid, fatty acid, and lipid. Moreover, signaling pathways involved in amino acid metabolism, energy metabolism, nucleotide synthesis, carbohydrate metabolites, and lipid biosynthesis were functionally disrupted by the SAEW at 40 ℃ treatment. As per our knowledge, this is the first research to uncover the potential mechanism of heated SAEW treatment against MRSA biofilm on food contact surface.